Electromechanical Transient Modeling of Modular Multilevel Converter based HVDC Network - Wang, Shuyao; Zhao, Xiaoying; Xue, Feng; Li, Wei; Peng, Huimin; Shi, Di; Wang, Siqi; Wang, Zhiwei (2019 IEEE Sustainable Power and Energy Conference (iSPEC), 2019)
The electromechanical model of modular multilevel converter (MMC) based high voltage dc (HVDC) transmission network in transient stability (TS) simulator is proposed in this paper based on the MMC average arm model and the submodule (SM) equivalent capacitance approach. The accuracy of the TS model is verified by comparing the simulation results with that of the PSCAD/EMTDC model subject to different grid contingencies, including the controller reference step change, the remote three-phase ground fault and the close three-phase ground fault.